KETERAMPILAN KOMUNIKASI PELAKU BISNIS BERBASIS KONSEP INDUSTRI 4.0 - AGUSTIN ROZALENA AGUSTIN ROZALENA (POLITEKNIK PIKSI GANESHA, 2018)
This study was conducted to construct a model of business communication skills by adopting the concept of industry 4.0. In an effort to build the work ethic of business communicators, soft skills and hardskills are expected to increase marketing and the growth of customer market networks across all industry lines.The purpose of this study, namely (1) to describe the model of business communication skills in the industrial era 4.0. (2) to find out some new professions with communication skills in the business world that are needed by stakeholders.The methodology of this study is qualitative with the paradigm of analyzing literature and documents. The researcher used document analysis with data analysis techniques using the interactive models of Miles and Huberman.The results of this study found (1) the concept of industry 4.0 was able to realize a business communication model with an internet base. (2) Communication skills play a role in supporting the emergence of new professions in digital business communication.